Hungary : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2005)
This report examines Hungary's Observance of Standards and Codes on the Financial Action Task Force (FATF) recommendations for Anti-Money Laundering (AML) and Combating the Financing of Terrorism. Hungary has a substantial AML legal and institutional framework for combating money laundering (ML), including preventive measures for a wide range of service providers and law enforcement measures. The ML offense, while it addresses self-laundering, covers only using the proceeds of crime in the business activity of the perpetrator or in a bank or financial transaction.